2014
DOI: 10.1016/j.pain.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

The sensory innervation of the calvarial periosteum is nociceptive and contributes to headache-like behavior

Abstract: Headaches are thought to result from the activation and sensitization of nociceptors that innervate deep cephalic tissues. A large body of evidence supports the view that some types of headaches originate intracranially, from activation of sensory neurons that innervate the cranial meninges. However the notion of an extracranial origin of headaches continues to be entertained, although the identity of deep extracranial cephalic tissues which might contribute to headaches remains elusive. Here we employed anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 33 publications
(48 reference statements)
0
86
0
Order By: Relevance
“…Because the up-regulated genes were linked to activation of mast cells, T cells and natural killer cells 43, 44 , production of cytokines, cell adhesion, cell-cell signaling, glycoprotein production 45 and disruption of proper NF-kB function 46, 47 , whereas the down-regulated genes were linked to repression of TNF-alpha, IL-6, and macrophage activation 48, 49 , and to prevention of cell lysis through inhibition of NK, T, and B cells 50 , we interpret these findings as suggesting that the molecular environment in which periosteal pain fibers exist is inflamed and that this localized inflammation can activate, or lower the activation threshold of trigeminal nociceptors that reach the affected periosteum through suture branches of intracranial meningeal nociceptors 51 and somatic branches of the occipital nerve 52 . Accordingly, we conclude that the localized extracranial pathophysiology we identified (i.e., periosteal inflammation) in the CM patients should be considered as evidence that some migraine attacks can originate outside the head.…”
Section: Discussionmentioning
confidence: 87%
“…Because the up-regulated genes were linked to activation of mast cells, T cells and natural killer cells 43, 44 , production of cytokines, cell adhesion, cell-cell signaling, glycoprotein production 45 and disruption of proper NF-kB function 46, 47 , whereas the down-regulated genes were linked to repression of TNF-alpha, IL-6, and macrophage activation 48, 49 , and to prevention of cell lysis through inhibition of NK, T, and B cells 50 , we interpret these findings as suggesting that the molecular environment in which periosteal pain fibers exist is inflamed and that this localized inflammation can activate, or lower the activation threshold of trigeminal nociceptors that reach the affected periosteum through suture branches of intracranial meningeal nociceptors 51 and somatic branches of the occipital nerve 52 . Accordingly, we conclude that the localized extracranial pathophysiology we identified (i.e., periosteal inflammation) in the CM patients should be considered as evidence that some migraine attacks can originate outside the head.…”
Section: Discussionmentioning
confidence: 87%
“…The exposed dura was bathed with a modified synthetic interstitial fluid (SIF) consisting of (in mM) 135 NaCl, 5 KCl, 1 MgCl 2 , 5 CaCl 2 , 10 glucose, and 10 HEPES at pH 7.2. Single-unit activity of meningeal nociceptors (1 U/rat) was recorded in the ipsilateral (left) trigeminal ganglion using a contralateral approach, as described recently (Zhao and Levy 2014) and see also Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…First, we recorded the activity of meningeal nociceptors in the trigeminal ganglion using an electrode that was inserted into the ganglion through the contralateral cortex (Zhao and Levy 2014), thus preventing a resultant CSD in the ipsilateral cortex. We further minimized the possibility of direct stimulation of meningeal nociceptors with RF over the transverse sinus by inducing CSD experimentally in the frontal cortex, a caudal cortical region covered by dural tissue that is innervated by only a small percentage of neurons that also have RF on the transverse sinus.…”
mentioning
confidence: 99%
“…Some have suggested that activation and sensitization of calvarial periosteal afferents could play a role in mediating secondary headaches such as post-craniotomy and PTH [75]. It is proposed that inflammatory evoked enhancement of peripheral cranial nociception, rather than changes in supraspinal pain mechanisms contribute to the initial development of PTH [76].…”
Section: Future Research Considerationsmentioning
confidence: 99%